PROTEIN REKOMBINAN 38 KDA MYCOBAKTERIUM TUBERKULOSIS DAPAT MENGIMBAS PEMBUATAN INTERLEUKIN-2 DAN INTERFERON-γ LIMFOSIT T DI KULTUR SEL MONONUKLEAR DARAH TEPI - Maimun Z Arthamin; Singgih Pujo Wahono; Antiek Primardianti; Ati Rastini; Tri Wahju Astuti; Tri Yudani Mardining Raras; Francisca S Tanoerahardjo (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2016)
Tuberculosis (TB) is caused by Mycobacterium tuberculosis (M.tb) and is one of the significant mortality causes WHO (2012). Theprimary immune response in TB pathogenesis is Cell Mediated Immunity (CMI), roled by T lymphocytes. Interleukin-2 (IL-2) is a growthfactor for T lymphocytes. Gamma Interferon is the key cytokine in M.tb infection control, synthezised by T lymphocytes. An effectivevaccination strategy is achieved by giving vaccine which is able to stimulate T lymphocytes in synthezising cytokines. The 38 kDa M.tbprotein is potential in the vaccine development program, because it has specific epitopes for T lymphocytes. The aim of this study was toknow how to determine that the 38 kDa recombinant protein of M.tb Malang strain could induce cellular immune response by IL-2 andIFN-γ synthezised by T lymphocytes. The study was carried out by an experimental in vitro study on PBMC from healthy endemic subjects,those having TB contact, and the TB patients themselves. PBMC from subjects was cultured with 38 kDa recombinant protein of M.tbMalang strain, with PPD and without any protein. The analysis of IL-2 and IFN-γ used flowcytometry. The result showed that the highestpercentage of IL-2 was found in the culture with 38 kDa recombinant protein of M.tb Malang strain, in healthy endemic (p=0.000)and in those who had TB contact (p=0.000). the highest percentage of IFN-γ was found in the culture with 38 kDa recombinant proteinof M.tb Malang strain, in healthy endemic (p=0.007) and those who had TB contact (p = 0.105). The 38 kDa recombinant proteinof M.tb Malang strain was able to induce IL-2 and IFN-γ synthezised by TCD3+ lymphocytes from healthy endemic subjects and thosewho had TB contact.